Development of In Vitro-In Vivo Correlation/Relationship Modeling Approaches for Immediate Release Formulations Using Compartmental Dynamic Dissolution Data from "Golem": A Novel Apparatus - Čulen, Martin; Tuszyński, Paweł K; Polak, Sebastian; Jachowicz, Renata; Mendyk, Aleksander; Dohnal, Jiří (BioMed research international, 2015)
Different batches of atorvastatin, represented by two immediate release formulation designs, were studied using a novel dynamic dissolution apparatus, simulating stomach and small intestine. A universal dissolution method was employed which simulated the physiology of human gastrointestinal tract, including the precise chyme transit behavior and biorelevant conditions. The multicompartmental dissolution data allowed direct observation and qualitative discrimination of the differences resulting from highly pH dependent dissolution behavior of the tested batches. Further evaluation of results was performed using IVIVC/IVIVR development. While satisfactory correlation could not be achieved using a conventional deconvolution based-model, promising results were obtained through the use of a nonconventional approach exploiting the complex compartmental dissolution data.
Keywords: Equipment and Supplies; Intestine, Small; uvolňování léčiv; Atorvastatin; atorvastatin; farmaceutická chemie; zdravotnické prostředky; lidé; Drug Liberation; gastrointestinální trakt; Humans; Chemistry, Pharmaceutical; Gastrointestinal Tract; tenké střevo